Treatment effectss after treated with PSU-Fixed functional appliance in class II malocclusion patients - Pimpalak Kawviriyakul (Prince of Songkla University, 2011)
Thesis (M.Sc., Oral Health Sciences)--Prince of Songkla University, 2008